Bias-Corrected Nonlinear Investment- q Relation in the Cross Section of Firms - Song, Suyong; Wee, Hyunbok (The Review of Corporate Finance Studies, 2026)
Abstract We study a nonlinear relationship between corporate investment and Tobin’s q in the cross section of firms. After correcting for nonlinear errors using a repeated measurement of q derived from analysts’ forecasts, we find evidence of varying investment-q sensitivity across firms. The investment-q sensitivity is low for firms with low q. It then becomes more pronounced at intermediate values before weakening at high values of q, resulting in an S-shaped pattern. In the cross section, the true investment-q relation is therefore not strictly linear. Firm investment is predicted to remain similar among firms with low q, suggesting that increases in q do not necessarily lead firms to increase investment significantly. (JEL C21, C26, E22, G31)